Analysis of the level of labor potential development in higher educational institutions of Ukraine: competitiveness of university graduates - Moroz, Volodymyr M.; Moroz, Svitlana A.; Moroz, M. V. (Henan science and technology press, 2016)
The article focuses on the possibility of using the criterion of competitiveness of domestic higher education institutions in the international labor market to analyze the level of development of labor potential of a particular university. In the article the relationship between the level of professional competence of future professionals and the quality of labor potential of universities which were involved in their formation and development. This article contains statistical information on the results of participation of Ukrainian university students in international student competitions, which the author used to characterize the quality of professional institutions in the field of competitiveness of future specialists. In addition, the article contains generalizations as for the possibility of usage the competitiveness feature level of graduates as an indicator (index) of the quality of university's labor potential.
Keywords: labor potential of university; competitiveness of university graduates; public administration; mechanisms of governing